Christianity and human rights: Christians and the struggle for global justice - Shepherd, Frederick M. (Lexington Books, 2009)
Introduction: The political and theological evolution of Christianity and human rights / Frederick M. Shepherd -- Past sins, future promise : overviews of Christianity and human rights -- Deliver us from evil : genocide and the Christian world / James Waller -- The best of times, the worst of times : a Dickensian era of religious rights / John Witte -- Religious freedom and human rights -- Toward a more comprehensive religious freedom / Johannes van der Ven -- The enduring alliance of religious freedom and democratic rights / Joseph Loconte -- Religious freedom and international law / Rpbert Drinan -- Democracy and human dignity / Jean Bethke Elshtain -- Theological and philosophical foundations for human rights -- Patrick Byrne, universal rights or personal relations / Patrick Byrne -- Human rights, the common good, and our supernatural destiny/ Dana Dillon -- Bozena Komarkova : toward an existential Christian philosophy of human rights / Joyce J. Michael -- Catholic social teaching, economic rights, and globalization / John Sniegocki -- Rights, capabilities, and human flourishing -- Case studies / Jonathan Warner -- The rights of the poor : Christian theology and human rights practices in Latin America's Andean Region / Thomas Bamat -- Christianity and human rights in Vietnam : the case of ethnic minorities (1975-2004) / James Lewis -- From human rights to human wrongs : the dramatic turn of the South African Pentecostal Movement on human rights issues / Nico Horn -- Conclusion: Concluding remarks on Christianity and human rights / Frederick M. Shepherd